Radiation Dose Optimization in Adult Head CT: A Comprehensive Review from Phantom-Based Evaluation to Clinical Implementation - Inganatul Islamiyah; Yuyun Yueniwati; Chomsin Sulistya Widodo; Zaenal Arifin (Journal of Physics and Its Applications, 2026)
The widespread use of head computed tomography (CT) has led to a significant increase in patient radiation dose. Although modern CT systems include dose-saving technologies, further optimization is necessary to balance radiation dose and image quality. This study aims to review dose optimization strategies in head computed tomography (CT), focusing on the impact of acquisition parameter modifications across different phantom types and their translation into clinical applications. Variations in radiation dose and image quality are quantitatively assesed using multiple phantoms. PMMA phantoms validates dose measurements, image quality phantoms enable comprehensive assessment of image metrics, and anthropomorphic phantoms ensure clinical relevance. In clinical applications, image quality is qualitatively evaluated by radiologists. Results show that tube voltage and tube current are the main strategies of dose optimization, supported by automatic exposure control, pitch adjustment, and reconstruction algorithms. Iterative reconstruction techniques effectively mitigate noise amplification due to the adjustments. Radiation dose reduction ranges from approximately 15% to 80%, depending on the applied parameter modifications. Since dose reductions often lead to increased image noise and variations in image quality, this review identifies the optimal range of parameter adjustments that maintain diagnostically acceptable image quality. Combining quantitative assessments with phantoms and qualitative evaluations by radiologists enables a more comprehensive understanding of optimization results that can greatly benefit clinical practice by serving as a long-term guideline for safe and effective head CT dose optimization.